Pengaruh Brand Awareness dan Brand Image terhadap Keputusan Pembelian Gen Z pada Produk SmartphoneSamsung di Kedoya Utara - Allya Agfara; Rudy P Tobing (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to analyze and determine the influence of brand awareness on partial purchase decisions, the impact of brand image on partial purchase decisions, and the simultaneous influence of brand awareness and brand image on Gen Z purchase decisions on Samsung smartphone products in North Kedoya. The sampling technique is cluster sampling with a total sample of 312 Gen Z respondents domiciled in North Kedoya, and the data collection technique uses a questionnaire distributed online. The research used statistical test instruments, namely, validity test, multicollinearity test, and heterodynes test. The data analysis technique uses Multiple Linear Regression, Classical Assumption Test, T test, F Test, and Coefficient of Determination. The research variables were Brand Awareness (X1), Brand Image (X2), and Purchase Decision (Y). The partial test results showed that brand awareness had a positive and significant effect on purchase decisions, and brand image had a positive and significant effect on purchase decisions. The simultaneous test results showed a simultaneous and significant influence between brand awareness and brand image on Gen Z's purchase decisions on Samsung smartphone products in North Kedoya.